Prepartum dietary energy source fed to beef cows: II. Effects on progeny postnatal growth, glucose tolerance, and carcass composition - Radunz, A. E. (2012)
Mature Angus-cross beef cows (n = 228) were used to evaluate effects of prepartum dietary energy source on postnatal growth and carcass composition of progeny in a 2-yr study. Starting at approximately 160 d of gestation, cows were fed diets consisting of 1 of 3 primary energy sources: grass hay (HY), corn (CN), or dried corn distillers grains with solubles (DG). The CN and DG diets were limit-fed to achieve similar energy intakes as cows fed HY. Following parturition, cows were fed a common diet and managed as a single group. Calves were weaned at an average of 185 ± 6 d of age and backgrounded for 28 d. A subset of progeny (n = 134) was individually fed a common finishing diet until slaughter, when each calf reached 1.2 ± 0.05 cm of backfat. A glucose tolerance test (GTT) was conducted in year 2 on 4 calves/treatment after 41 and 111 d on the finishing diet (DOF). Calf birth weights were greater (P = 0.002) in calves from cows fed CN and DG than calves from cows fed HY, and weaning BW (P = 0.08) was less for calves from cows fed HY vs. CN. Receiving BW, final BW, and HCW did not differ (P ≥ 0.16) among treatments. No difference (P ≥ 0.28) in ADG, morbidity, and mortality from birth to slaughter was observed among treatments. In response to a GTT, increased DOF resulted in greater (P ≤ 0.005) fasting insulin, faster glucose disappearance rate, and greater insulin:glucose area under the curve ratio. Glucose disappearance rate was greater (P = 0.01) in calves from cows fed CN than in calves from cows fed HY or DG. A greater initial insulin response (P = 0.005) was observed in calves from cows fed CN or DG than in calves from cows fed HY. Carcass traits used to measure yield grade did not differ (P ≥ 0.19) among treatments. Calves from dams fed CN had the lowest marbling score (P = 0.03) and intramuscular fat content (P = 0.07). These results indicate that prepartum maternal dietary energy source can alter fetal adipose tissue development and insulin sensitivity resulting in long-term effects on progeny's intramuscular fat deposition. Moreover, present findings suggest that increasing the number of days on a corn-based finishing diet increases insulin resistance in beef cattle.